2003
DOI: 10.1046/j.1365-3156.2003.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of community‐based vs. institutional‐based direct observed short‐course treatment for the control of tuberculosis in Kilombero district, Tanzania

Abstract: SummaryTuberculosis (TB) has reappeared as a serious public health problem. Non-compliance to antituberculous drug treatment is cited as one of the major obstacles to the containment of the epidemic. Compliance may be optimized by Directly Observed Treatment (DOT) and short-course treatment regimens. Since 1986, Tanzanian TB patients have received daily DOT at health facilities for the first 2 months of the treatment course. However, adherence and cure rates have been falling as the number of TB cases continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 14 publications
2
75
2
2
Order By: Relevance
“…Cost of treatment was also identified as a factor defining the use of the DOTS clinics in the study area. These agree with findings from other studies (Olumuyiwa et al, 2004;Lwilla et al, 2003;Enwuru et al, 2002;Auer et al, 2000;Wandwalo & Mørkve, 2000;Marinac et al, 1998;Needham et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Cost of treatment was also identified as a factor defining the use of the DOTS clinics in the study area. These agree with findings from other studies (Olumuyiwa et al, 2004;Lwilla et al, 2003;Enwuru et al, 2002;Auer et al, 2000;Wandwalo & Mørkve, 2000;Marinac et al, 1998;Needham et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Being principally a disease of poverty, Tuberculosis (TB) is one of the oldest leading causes of morbidity and mortality and remains one of the deadliest communicable diseases in human history globally [1] [2]. It is caused by Mycobacterium tuberculosis (M. tuberculosis) and is an important public health concern [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies have shown that community-based DOT is a cost-effective strategy that yields treatment outcomes similar to those obtained with facility-based DOT. [3][4][5][6] However, community-based DOT has been criticized for being beyond the control of health-care providers and hence conducive to self-administered (unsupervised) treatment and non-adherence. 6,7 The actual degree of adherence by patients on communitybased DOT has not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%